Suitability of On-Farm Green Compost for the Production of Baby Leaf Species - Enrica De Falco (MDPI AG, 2021)
This study evaluated, for the first time, the suitability of on-farm green compost (GC) from the fourth range sector for the production, in a controlled environment, of six baby leaf species (radish, lettuce, rocket, chard, sorrel and dill), characterized by short cultivation cycles. The pH and electrical conductivity of potting soil-compost mixtures were affected by the different amounts of GC added to the potting soil. Germination tests on Lactuca sativa seeds indicated no phytotoxic effects when GC was used to prepare aqueous extracts diluted at 50% and 25% (v/v). In the pot experiment, GC was used at four different dosages in the growing medium, inducing different impacts on growth parameters, depending on the species and applied dose. The greatest plant growth responses were determined by using less than 3.5 g of GC in 100 g of potting soil. Significant positive correlations between the dry weights of root and shoot (r = 0.77 **), seedling height (r = 0.51 **) and the number of true leaves number (r = 0.56 **) confirmed the close relationship between the root system biomass and the growth parameters of aboveground organs. The study highlights that on-farm green compost, used as partial growing substrate, provides a good opportunity to obtain baby leaf species with well-developed root systems.